2007
DOI: 10.1128/mcb.01476-06
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α1β1 Controls Reactive Oxygen Species Synthesis by Negatively Regulating Epidermal Growth Factor Receptor-Mediated Rac Activation

Abstract: Integrins control many cell functions, including generation of reactive oxygen species (ROS) and regulation of collagen synthesis. Mesangial cells, found in the glomerulus of the kidney, are able to produce large amounts of ROS via the NADPH oxidase. We previously demonstrated that integrin ␣1-null mice develop worse fibrosis than wild-type mice following glomerular injury and this is due, in part, to excessive ROS production by ␣1-null mesangial cells. In the present studies, we describe the mechanism whereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 60 publications
8
95
0
Order By: Relevance
“…3 They play opposite functions when activated by collagen, and they can also affect the functions of the other. 26 Although loss of integrin a1b1 leads to increased levels of EGF receptor activation, ROS production, and consequent collagen synthesis/deposition compared with WT cells and/or mice, 3,6,7 loss of integrin a2b1 does not seem to have a protective role because of decreased EGF receptor activation or ROS production; no differences in EGF receptor phosphorylation (not shown) or ROS levels ( Figure 5C) were observed between WT and integrin a2-null cells.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…3 They play opposite functions when activated by collagen, and they can also affect the functions of the other. 26 Although loss of integrin a1b1 leads to increased levels of EGF receptor activation, ROS production, and consequent collagen synthesis/deposition compared with WT cells and/or mice, 3,6,7 loss of integrin a2b1 does not seem to have a protective role because of decreased EGF receptor activation or ROS production; no differences in EGF receptor phosphorylation (not shown) or ROS levels ( Figure 5C) were observed between WT and integrin a2-null cells.…”
Section: Discussionmentioning
confidence: 88%
“…6 Briefly, 1.5310 5 primary WT, a1-null, and a2-null mesangial cells were plated in sixwell plates in DMEM containing 10% FCS. After 2 days, the cells were washed and incubated in serum-free medium with 2 mM dehydroethidium (Sigma).…”
Section: Ros Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, integrin α1 is expressed at low levels in human breast cancer cell lines (18) and is downregulated in breast and ovarian cancer (19), suggesting that its loss might be associated with malignancy. Furthermore, integrin α1 can negatively regulate EGFR signaling in prostate and cervical cancer cells (20) as well as in mesangial cells (21). In the present study, a cell adhesion blocking assay showed that anti-CD49a (integrin α1 subunit) mAb significantly reduced the adhesiveness of the clones compared to the controls.…”
Section: Discussionmentioning
confidence: 63%